TOWARDS MODEL‐BASED SYSTEMS ENGINEERING (MBSE) PATTERNS TO EFFICIENTLY REUSE KNOW‐HOW. Issue 4 (28th December 2017) - Wu, Quentin; Gouyon, David; Hubert, Pascal; Levrat, Éric
ABSTRACT: Know‐how reuse is an approach that has been always used by engineers to take advantage of their accumulated knowledge and practices. But, the difficulty to formalize and reuse expert know‐how is increasing alongside the complexity of systems. To deal with this challenge, this paper aims to open the way to new approaches of know‐how reuse, in order to improve engineering activities. For that purpose, it explores the capabilities of three reuse approaches (commercial off‐the‐shelf (COTS), set‐based design, and patterns), and their ability to be linked with a model‐based systems engineering (MBSE) framework.